CALON MEMPELAI PEREMPUAN MELAMAR CALON MEMPELAI LAKI-LAKI (TRADISI LAMARAN CALON PENGANTIN yang Berlaku di Trenggalek) - yatmin, yatmin (Nusantara of Research : Jurnal Hasil-hasil Penelitian Universitas Nusantara PGRI Kediri, 2016)
ABSTRACTIn each society has different wedding ceremony. This is influenced by several factors including, race, ethnicity, culture, religion or social background. One of the application process is the earliest in a relationship men and women to bind to each other, in every region on the island of Java was also not the same. Some areas in East Java, especially in Trenggalek practice of Javanese wedding held unlike in other regions, where the region is not the groom who applied first, but the opposite is applying for first is the prospective bride. But with the changing times and technology and human relations increasingly widespread traditions also change and adapt to the changing times, which means that the tradition is not entirely to be carried on like that but depending on the circumstances, why this is so because the tradition is a human product so that it suitable definitely retained and carried on and when not matched certainly the fox. Key Words: Application, Women, Men